1998
DOI: 10.1080/02827589809383003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silvicultural cleaning in mixed pine‐deciduous stands on moose damage to scots pine (Pinus sylvestris)

Abstract: Silvicultural cleaning is commonly carried out in young stands to control competition between conifers and deciduous tree species. However, it has been questioned whether this practice affects moose (Alces alces L.) browsing on Scots pine (Pinus sylvestris L.) with respect to damage at the stand level. In this study, moose winter browsing was examined in relation to food availability in 19 Scots pine stands divided into silviculturally cleaned and non-cleaned blocks. Cleaning had a negative effect on moose for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…The amount of birch browse did not significantly affect Scots pine damage, in agreement with results by Ball and Dahlgren (2002) and Härkönen (1998), but the height relation between the species did. Damage increased when birch overtopped pine.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The amount of birch browse did not significantly affect Scots pine damage, in agreement with results by Ball and Dahlgren (2002) and Härkönen (1998), but the height relation between the species did. Damage increased when birch overtopped pine.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results have been reported previously (e.g. Heikkilä 1990Heikkilä , 1993Heikkilä and Härkönen 1996;Härkönen 1998;Härkönen et al 2008b;Nikula et al 2008). Scots pine is a light demanding tree species, and shading reduces its height-and diameter growth, keeping the trees longer within moose browsing range and, possibly, making them more palatable to moose (Danell et al 1991b).…”
Section: Discussionsupporting
confidence: 88%
“…Also, from the point of view of silvicultural treatment, our results suggest that the cleaning of deciduous trees should preferably be performed in the immediate vicinity of those pines to be grown to the end of the rotation further rather than applied to the whole stand (Härkönen 1998).…”
Section: Discussionmentioning
confidence: 92%
“…Studies on the effect of deciduous trees on moose browsing have, in general, shown that although deciduous tree species that are favoured by moose increase the total consumption of biomass in stands, pine browsing is only slightly affected by the presence of other tree species (Danell et al 1991, Edenius 1991. The results from inventory-based studies have also indicated that the total cleaning of deciduous trees from pine plantations might even have a detrimental effect if the amount of alternative food is not increased (Heikkilä 1991, Härkönen 1998. Our results are thus in line with previous studies, since none of the deciduous tree species nor the total amount of deciduous trees per se affected browsing probability.…”
Section: Discussionmentioning
confidence: 99%
“…At the level of a plantation, at least tree species mixture (Heikkilä 1990;Heikkilä 1991;Härkönen 1998;Härkönen et al 1998;Kullberg and Bergström 2001;Härkönen et al 2008;Milligan and Koricheva 2013) and the density of trees (Lundberg et al 1990;Heikkilä 1991;Lyly and Saksa 1992;Ball and Dahlgren 2002) have been found to partly explain damage. Other factors at the plantation level that have been associated with damage are the fertility of the site (Niemelä and Danell 1988;Ball and Dahlgren 2002;Bergqvist et al 2014) and fertilization (Löyttyniemi 1981;Edenius 1993;Ball et al 2000).…”
Section: Factors Affecting Damage At the Plantation Levelmentioning
confidence: 99%